A Comparative Case Study: Does the Organization of Primary Health Care in Brazil and Turkey Contribute to Reducing Disparities in Access to Care? - Ece A. Özçelik; Adriano Massuda; Marcia C. Castro; Enis Barış (Taylor & Francis Group, 2021)
Brazil and Turkey are among the few high-middle-income countries that explicitly chose to strengthen their primary health care (PHC) systems as the centerpiece of much broader health system reforms aiming to narrow inequities in access to care. This comparative case study reviews the organization of Brazil and Turkey's PHC systems to derive lessons that can apply to other countries that may consider reforming the organization of PHC systems as a way to address health inequities. The analysis uses the Flagship Framework to investigate how the organization of PHC delivery in Brazil and Turkey can lead to measurable improvements in access to care. It compares (1) the degree of decentralization in PHC service delivery responsibilities, (2) the use of multi-professional PHC teams, and (3) patient impanelment strategies. The comparative analysis offers three important lessons. First, changes in the organization of PHC systems can contribute to observable improvements in the level and distribution of health outcomes, but organizational strategies do not guarantee eliminating disparities in access. Second, PHC systems can operate in health systems with varying degrees of decentralization, but the level of decentralization may influence implementation. Third, relying on multi-professional PHC teams that serve geographically empaneled populations can improve equitable access to care, but course corrections may be needed to address evolving health demands.